UKURAN RISIKO ATAS PERTANGGUNGAN DENGAN BESAR KLAIM YANG TERMODIFIKASI - Aprida Siska Lestia (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
Coverage modifications results in the amount of payment or reimbursement of claims not being the same as that proposed by the policyholder. Determination of the deductible causes claims below that value to be borne by the policyholder. Meanwhile, setting a policy limit results in a maximum value for claims borne by the insurance company (maximum covered loss). The size of risk as an important value in risk management, which in its determination depends on the distribution of losses in the form of claims, will also be affected by coverage modifications. In this study, risk measure was determined based on the standard deviation and value at risk that using quantile values. In addition, a risk measure is also determined in the form of a conditional tail expectation which is the average value of the loss over a certain quantile and the risk measure is based on a proportional hazard transformation. The size of the risk is determined by the coverage modified by the deductible and policy limit. Apart from that, it is also taken into account that there may be inflation, which of course will also have an impact on the distribution of claims. The observed claim size is known to have a Weibull distribution with certain parameter values, which heavy tailed. The results obtained indicate that modifications in the form of setting deductibles and policy limits have an impact on the magnitude of all risk measures obtained.